PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MEMAHAMI TEKS BACAAN SISWA KELAS III SD NEGERI 011 PULAU RAMBAI KECAMATAN KAMPAR TIMUR - Melga Sari Melga Sari; Otang Kurniaman Otang Kurniaman; Zulkifli Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The problem of research is low reading skills students understand the text, it can be see from the average value of student is 64.17. of the 12 students who achieve grades above KKM just 5 students (41%), while student who have not reached the KKM were 7 students (58%), the value specified KKM is 70. Based on these problems need to be done with the class action research applying the direct learning model. This study aims to improve the skills of reading text understanding Elementary School third grade student Pulau Rambai 011 Academic Year 2015/2016 the number of students as many as 12 people consisting of 5 boys and 7 girls. The study was conducted by two cycles. At each cycle I and II consist of three meetings, wich consists of two face to face meetings and one times dayli test at the end of the cycle. With applied learning models can improve the skills understanding direct reading student text, it is see from the increase of student writing skills base score is an average of 64.17, in the first cycle increased to 70.42 and the second cycle increased to 77.92. the percentage of teacher acvtivity also increased, as see from the percentage of the activity of teachers in the first cycle the first meeting 60% increase in the second meeting to 70%, in the second cycle increased in the first meeting, namely 80% and increased in the second meeting to 85%. The percentage of student activity also increased in the first cycle of the first meeting 55% increasing to 65% in the second meeting, on the second cycle increased at a first meeting 75%, and increased in the second meeting 80%. Based on the result of the study concluded that the implementation of direct learning model can improve the reading skills to understand the text of the third grade students of public Elementary School 011 Pulau Rambai.Key words: Direct Learning Model, Understanding Text